L’Élevage et l’Utilisation des Animaux Pendant le Néolithique Moyen à Vadastra (Roumanie) - Ghetie, Basile; Mateescu, Cornéliu (Zephyrvs, 2009)
RESUMEN: Con el desarrollo del óptimo climático en el Bajo Danubio, se produce una expansión de las formas de vida. En el Neolítico medio, algunas familias, cuya prinepal ocupación era la domesticación y la agricultura, se establecieron en VSdastra, donde el medio natural les ofrecía numerosas posibilidades de existencia. En VSdastra 1 los huesos de animales domesticados pertenecen a las siguientes especies: bóvidos (casi el 60 %); animales ovinos (casi el 20 %) y el resto de animales caprinos, porcinos, y cánidos. Durante el Vadastra II, los huesos de animales domésticos pertenecientes a las mismas especies, se han encontrado en grandes cantidades. Ello es explicable por un proceso de desarrollo de la comunidad paralelo a un desarrollo económico. En esta época se introduce el caballo como animal de silla. El estudio de los huesos de los animales domesticados, descubiertos en Vadastra y otros yacimientos nos ha permitido un mejor conocimiento relativo a la utilización de animales durante el Neolítico medio en el Bajo Danubio testimonio del progreso económico en el V milenio a. C. ABSTRACT: When the climatic Optimum developed on the Lower Danube, the populations began to spread. In the Middle Neolithic a few families of cattle breeders and tillers of the soil settled at Vadastra. on Mãgura Fetelor (Maidens’Hillock) and on Dealul Cismelei (Fountain’s Hill) as the geo-biotic environment afforded favourable living conditions. And in order to place their possessions —particularly the cattle— in safety, the settlement was surrounded by a ditch, playing the same part as a fence. In the Vadastra I phase the bones of domestic animals belong to the following species: bovines (circa 60 %), ovine animals (circa 20 %) and the rest caprine animals, porcines, canine animals. The bovines were bred for milk, flesh, hides and bones but particularly as traction animals for farming. The ovine or caprine animals were bred in the first place for hides, wool and hair used to make clothing. The porcines were bred for flesh and fat while the canine animals were used as watch animals and consumption animals. During the Vadastra II phase, the bones of domestic animals belong to the same species, but they have been found in very large numbers. This is accounted for, perhaps by the growing demands of a more numerous community, in full economic progress. It was now the moment the horse was known, used for riding. The study of the bones of domestic animals discovered at Vadastra and in other settlements (fig. n.° 1) has led to more better knowledge regarding the utilisation of animals during the Middle Neolithic on the Lower Danube accounting also for the economic progress in the 5th millenium B.C.